The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1093/mnras/sty2040
|View full text |Cite
|
Sign up to set email alerts
|

The changing GMC population in galaxy interactions

Abstract: With the advent of modern observational efforts providing extensive giant molecular cloud catalogues, understanding the evolution of such clouds in a galactic context is of prime importance. While numerous previous numerical and theoretical works have focused on the cloud properties in isolated discs, few have looked into the cloud population in an interacting disc system. We present results of the first study investigating the evolution of the cloud population in galaxy experiencing an M51-like tidal fly-by u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 85 publications
(120 reference statements)
6
20
0
Order By: Relevance
“…vi) Comparison of the physical properties of clumps located within spiral arms and inter-arm regions reveals that clumps residing within inter-arm regions have, on average, lower velocity dispersions, virial parameters, and excitation temperatures. This difference in linewidths is in agreement with the smoothed particle hydrodynamics simulation of Duarte-Cabral & Dobbs (2016), and the difference in virial parameters is concordant with the findings of Pettitt et al (2018). vii) The median value of the radius distribution for clumps within the Sagittarius spiral arm is significantly higher than that of the Scutum-Centaurus spiral arm, though we can not exclude the possibility that this is partially a result of detecting more extended structure in the nearer Sagittarius arm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…vi) Comparison of the physical properties of clumps located within spiral arms and inter-arm regions reveals that clumps residing within inter-arm regions have, on average, lower velocity dispersions, virial parameters, and excitation temperatures. This difference in linewidths is in agreement with the smoothed particle hydrodynamics simulation of Duarte-Cabral & Dobbs (2016), and the difference in virial parameters is concordant with the findings of Pettitt et al (2018). vii) The median value of the radius distribution for clumps within the Sagittarius spiral arm is significantly higher than that of the Scutum-Centaurus spiral arm, though we can not exclude the possibility that this is partially a result of detecting more extended structure in the nearer Sagittarius arm.…”
Section: Discussionsupporting
confidence: 90%
“…In such an environment, the emission associated with a particular molecular cloud is more likely to overlap in position-position-velocity space, and therefore introduces an apparent increase in velocity dispersion. The lower virial parameters in the inter-arm regions is reminiscent of the simulations of tidally-induced spiral arms of Pettitt et al (2018), who found that the least-bound GMCs show a strong preference for residing within spiral arms, while the most bound ones exhibit a much weaker correspondence. Some of the bound inter-arm GMCs were found to be remnants of larger complexes within the spiral arms, although there were also a population that had formed in situ.…”
Section: Variations Between Arm and Inter-arm Regionsmentioning
confidence: 75%
“…In this section we show the mass spectra from the simulations and observations. We also fit a truncated power law to the mass function as described in Pettitt et al (2018). In this formalism the slope of the mass function is denoted γ, and we list γ for the mass distributions found using the friends of friends algorithm, and the observations in Table 2 (as well as denoting them on the relevant figures).…”
Section: Mass Spectramentioning
confidence: 99%
“…However this is a fairly extreme case involving a galaxy collision leading to particularly massive clouds and clusters. Pettitt et al (2018) compared the properties of GMCs formed in their simulations with M51, although the surface densities and interaction were not chosen to particularly match the M51 interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, advances in numerical methods led to cosmological scale simulations that can resolve GMC scale objects (∼ 10 5 M ), allowing a more faithful comparison, and potentially allowing us to follow their evolution through cosmic time and account for the effects of events such as galaxy mergers. So far, only a few such studies have been done, most of which concentrate on comparing the properties of clouds identified in the simulations to the present day observable GMCs (e.g., Pettitt et al 2018;Dobbs et al 2019, see Oklopčić et al 2017 for a high-redshift comparison).…”
Section: Introductionmentioning
confidence: 99%